Acute intermittent porphyria: Diagnostic dilemma and treatment options - Mohan Deep Kaur; Nita Hazarika; Namita Saraswat; Rajesh Sood (Wolters Kluwer Medknow Publications, 2015)
Acute intermittent porphyria (AIP) presents with diverse group of symptoms making its early diagnosis difficult. Delaying diagnosis and treatment of AIP can be fatal or can cause long term or permanent neurological damage. We present here a case report of AIP where the diagnosis was missed. The diversity of symptoms and details concerning the treatment options for AIP are discussed.